Effect of gibberellic acid on ripening of strawberry fruits (Fragaria annanassa Duch.) - Martínez, Gustavo Adolfo (1994)
Effect of GA3 on postharvest ripening in strawberry fruit was evaluated through different biochemical parameters. Strawberry slices at different ripening stages were incubated with GA3. A significant decrease on respiratory activity depending on GA3 concentration was obtained. Also GA3 was applied to whole and deachened fruit at white and green ripening stages. Our results show that GA3 has an inhibitory effect on strawberry fruit ripening, evidenced by a decrease in the respiratory activity and a delay in anthocyanin synthesis and chlorophylls degradation.